Investigation of Laurus Tamala leaves extract as an environmentally acceptable corrosion inhibitor for soft steel in 1M HCl: Electrochemical, DFT, and surface characterization techniques (Indian Journal of Chemical Technology (IJCT), 2023)
Laurus Tamala leaves extract (LTLE) has been employed as a soft steel corrosion inhibitor in a 1M Hydrochloric acid media. Chemical (weight loss) and electrochemical investigations were carried out to assess the corrosion rate and percentage inhibition efficiency of the extract. The electrochemical polarization results have demonstrated that plant leaves extract functions as a mixed type inhibitor. The stability of the inhibitor is tested at elevated temperatures by weight loss method. The corrosion inhibition mechanism is interpreted through adsorption mechanism, and the LTLE components has obeyed the Langmuir adsorption isotherm for soft steel. The interaction of the components of the extract is assessed through FT-IR technique. The surface morphology, roughness and hydrophobicity in presence and absence of the extract have been characterized through SEM, AFM and water contact angle techniques respectively. The highest inhibitory efficiency is 96.21% for 24 h as recorded by weight loss method. Additionally, the DFT computations has revealed the inhibitor’s adsorption through electron donor-acceptor interactions.